Solid‐State Hybrid Supercapacitor Assembled from a Heterostructured Co−Ni Battery‐like Cathode and Supercapacitor‐Type Highly Disordered Carbon Nanosheets. Issue 2 (17th January 2020) - Li, Zhan; Ma, Kongjun; Mi, Hongyu; Ji, Chenchen; Li, Zhiwei; Guo, Fengjiao; He, Shixue; Wang, Conghui; Xu, Mengjiao; Pang, Huan
Abstract: Hybrid at either the mechanism or the device level can lead to a hybridization effect of the kinetics and electrochemical characteristic of a supercapacitor (SC). Herein, a heterostructured NiCo2 S4 /Co x Ni1‐ x (OH)2 battery‐like cathode material was designed, with which the obtained sample accomplished the combination of excellent electronic and ionic conductivity so as to realize an enhanced faradaic redox storage process. Besides, a SC‐type highly capacitive anode material of a N and S co‐doped porous carbon nanosheets (ACNS) was also fabricated, which exhibits great advantages in terms of its enlarged specific surface area, the ease of introducing pseudocapacitive reactions, and its physical structure. These features directly lead to significant improvements in the electric double‐layer capacitor (EDLC)‐type electrochemical properties of the carbon anode. The combination of an EDLC‐type carbon anode with the redox‐reaction‐type cathode in a full cell device could potentially lead to a charge storage process that simultaneously integrates the electrophysical and electrochemical processes. For these reasons, the obtained solid‐state hybrid SC delivers a wide voltage window of 1.6 V, a high specific capacity of 121.3 C g −1, and enhanced energy/power densities of 26.1 Wh kg −1 /11 kW kg −1 . The as‐assembled device can maintain a high and stable capacity retention of 89.1 % for over 10 000 cycles. The developed hybrid assembly strategy and the electrode combination may provide design guidelines for designing other high‐energy hybrid SCs. Abstract : LED the way : A solid‐state hybrid supercapacitor (HSC) is assembled by using a multicomponent complex heterostructured NiCo2 S4 /Co x Ni1‐ x (OH)2 (TMS/TMH) cathode and biomass‐derived heteroatom‐doped highly disordered porous carbon nanosheets (ACNSs) as the anode. The HSC exhibits a favorable capacity with high energy/power output (sufficient to power an LED or electronic timer) and long‐term stability.